Individual Readiness for Change: The Impact of Person-Organization Fit and Psychological Ownership in Organizational Contexts - Insan, Muhammad Yalzamul; Batubara, Soulthan Saladin; Munisa, Munisa; Putri, Nurmala Tania (International Review of Management and Marketing, 2025)
The present study explores the role of person-organization fit (POF) and psychological ownership (PO) in shaping readiness for change (RFC) among lecturers at private universities in Indonesia. POF, reflecting the congruence between individual and organizational values, is posited to foster a sense of belonging and encourage active participation in change initiatives. Meanwhile, PO, defined as an individual’s sense of possession and responsibility, is expected to enhance commitment to organizational goals. Using a cross-sectional survey design, data were collected from 282 lecturers to analyze these relationships. The findings indicate that POF significantly influences both PO and RFC, while PO strengthens RFC and mediates the relationship between POF and RFC. These results highlight the importance of value alignment and psychological ownership in fostering readiness for organizational change. Practically, the study underscores the necessity for academic institutions to align their values with those of faculty members and cultivate a sense of ownership to facilitate effective change processes. However, the study is limited by its focus on private universities and the use of self-reported data, which may impact generalizability. Despite these limitations, the research contributes to the discourse on organizational change, encouraging further studies on POF and PO across varied contexts and outcomes.